2013
DOI: 10.4193/rhin12.147
|View full text |Cite
|
Sign up to set email alerts
|

Septorhinoplasty by disarticulation: early assessment of a new technique for morphological correction of crooked noses

Abstract: SummaryObjective: This study was aimed to assess the early morphological results of a new septorhinoplasty technique based on disarticulation (SRD) between bony and cartilaginous nose structures. Methodology:A retrospective, multi-judge, blind comparison of pre-and post-operative photographs displayed on Google documents © was designed. A nasal morphology analysis grid based on 10 items was ful lled independently by 6 judges to assess pre-and post-operatively, two times with a 15 day interval, the severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Type 3 PR: Cartilaginous-Only DP Procedure: Nasal Bony-Cartilaginous Disarticulation and Cartilaginous Push-Down Three authors Ishida et al, 21 Jankowski, 22,23 and Ferreira et al 24 have suggested dorsum lowering through nasal bony-cartilaginous disarticulation as their preferred technique. Saban 25 presented this technique limiting it to difficult noses.…”
Section: Type 2 Pr: Dorsum Preservation Procedures With Bony Cartilaginous Vault Resurfacingmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 3 PR: Cartilaginous-Only DP Procedure: Nasal Bony-Cartilaginous Disarticulation and Cartilaginous Push-Down Three authors Ishida et al, 21 Jankowski, 22,23 and Ferreira et al 24 have suggested dorsum lowering through nasal bony-cartilaginous disarticulation as their preferred technique. Saban 25 presented this technique limiting it to difficult noses.…”
Section: Type 2 Pr: Dorsum Preservation Procedures With Bony Cartilaginous Vault Resurfacingmentioning
confidence: 99%
“…First described by Ishida et al 22 and known as "cartilage-only push-down" this can create an open roof where the overlying nasal bones are removed and cartilage irregularities. To avoid these problems and broaden the spectrum of the cartilaginous push-down technique, Ishida et al 32 preserve the whole DKA during dorsum reduction and performs a "DKA pushdown."…”
Section: Nasal Hump Reduction Preserving Only the Cartilaginous Vaultmentioning
confidence: 99%
“…I commend the authors on an interesting and wellwritten manuscript comparing effects of classic hump resection rhinoplasty versus dorsal preservation rhinoplasty on the internal nasal valve angle and cross-sectional area as measured radiographically. Dorsal preservation rhinoplasty (DPR) has become a hot topic in the last several years with a number of prominent proponent's worldwide [1][2][3][4][5][6]. Among the suggested advantages of DPR is the maintenance of the keystone area anatomy, thus eliminating the need for reconstruction of the middle cartilaginous vault after lowering the dorsum by classic hump resection rhinoplasty [7].…”
mentioning
confidence: 99%
“…8 Several modifications have been described to preserve the cartilaginous structure of the dorsum when lowering its profile, by either detaching the cartilaginous dorsum including the upper lateral cartilages from the underlying septum, or by disarticulating the entire cartilaginous nasal skeleton from the bony nose. [9][10][11] In patients with a very thin skin, the risk of visible irregularities of the dorsum causing an operated appearance is clearly elevated even after meticulous reconstruction of the middle third. Conversely, preservation of the middle third may not be sufficient if the middle third is esthetically displeasing or a marked imbalance between the tip and the dorsum calls for its modification.…”
mentioning
confidence: 99%